A daily physical activity and diet intervention for individuals with type 2 diabetes mellitus: a randomized controlled trial - Agatha J. Van Rooijen; Christa M. Viviers; Piet J. Becker (AOSIS, 2010)
Urbanisation,  a  sedentary  lifestyle  and  increasing  obesity  due  to westernization and changed eating habits have been identified as independent risk factors for diabetes in the South African population. To establish the effectiveness of a daily walk and diet education intervention program. A randomized controlled trial was performed. The study population consisted of men and women of all races, ages 40 to 65 with Type 2 Diabetes Mellitus (DM) of duration at least one year attending the Steve Biko Diabetes Outpatient clinic. Patients of all weights were considered. Patients who had an HbA1c > 8 - 9.5% were included in the sample group.Four  weekly  group  classes  consisted  of  education  considered  essential  for  ongoing  nutrition  self-management  and physical activity. Yamax pedometers and walk prescriptions based on the average number of steps walked in three days were used. The participants had a follow-up assessment at 16 weeks and one year. The intervention and control groups were compared with respect to changes from baseline, using analysis of covariance (ANCOVA) with baseline values as covariates.The  difference  between  the  intervention  and  control  groups  in  the  change  in  HbA1c  from  the  baseline  was significant at the 16-week follow-up assessment (p=0.041) and in the total cholesterol and LDL-cholesterol at the  one-year follow-up assessment (p =0.047; p =0.014). These results suggest that HbA1c can be improved over a period of four months. More frequent contact with the patients is necessary.